2019
DOI: 10.3390/insects11010015
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of Sex Pheromone Mass Trapping Technology for Ectropis grisescens: A Potential Integrated Pest Management Strategy

Abstract: Since the identification of the Ectropis grisescens sex pheromone, no effective control technology based on this pheromone has yet been developed and evaluated. In this study, pheromone proportion and dosage, sustained-release dispensers, and pheromone lure-matched traps were optimized. The mass trapping technology developed with the above optimized parameters was tested in a field trial. The results show that two compounds, (Z,Z,Z)-3,6,9-octadecatriene and (Z,Z)-3,9-cis-6,7-epoxy-octadecadiene, at a ratio of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…The addition of host bean volatile increased attractiveness in 2015, supporting conclusions drawn by Evenden et al (2016) and St. Onge et al (2018); however, this trend was not observed in 2016. In addition to the semiochemical blend used in lures, lure type and dose can affect the number of insects captured in traps (Jansson et al 1993; Byers 2013; Luo et al 2020; Ebbenga et al 2022; Batallas and Evenden 2023). Surprisingly, pheromone dose (10 mg versus 21 mg) and lure type (septa versus microcentrifuge tube, respectively) had no effect on the abundance of S. lineatus captured in 2016.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of host bean volatile increased attractiveness in 2015, supporting conclusions drawn by Evenden et al (2016) and St. Onge et al (2018); however, this trend was not observed in 2016. In addition to the semiochemical blend used in lures, lure type and dose can affect the number of insects captured in traps (Jansson et al 1993; Byers 2013; Luo et al 2020; Ebbenga et al 2022; Batallas and Evenden 2023). Surprisingly, pheromone dose (10 mg versus 21 mg) and lure type (septa versus microcentrifuge tube, respectively) had no effect on the abundance of S. lineatus captured in 2016.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely known that the unique characteristics of insect pheromones, such as high specificity, low toxicity, activity at very low concentrations, and rapid degradation in the environment, make them ideal tools within integrated pest management (IPM) programs (Klassen et al, 2023;Rizvi et al, 2021). For example, dispensers emitting volatile pheromones in the field are used for monitoring and managing pests, by means of mass trapping, mating disruption, "attract-and-kill" and in "push-pull" strategies (Carleton et al, 2020;Cruz-Esteban et al, 2022;Dhanyakumar et al, 2020;Fountain et al, 2021;Gregg et al, 2018;Hassemer et al, 2019;Howse et al, 1998;Luo et al, 2019). Allelochemicals are also used within IPM programs.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 The use of mating disruption and trapping strategies that employ area-wide application of sex pheromones to manage E. grisescens populations has become a promising alternative to pesticide applications. 13,14 Nevertheless, in practical application, multi-component sex pheromones are costly to prepare or unstable under field conditions. Also, the ratio and concentration of the pheromone blend components need further research to keep the bait efficient in long-term usage.…”
Section: Introductionmentioning
confidence: 99%